Osmoregulation of gene expression in Salmonella typhimurium: proU encodes an osmotically induced betaine transport system. - Cairney, J (1985)
Previous evidence has indicated that a gene, proU, is involved in the response of bacterial cells to growth at high osmolarity. Using Mu-mediated lacZ operon fusions we found that transcription of the proU gene of Salmonella typhimurium is stimulated over 100-fold in response to increases in external osmolarity. Our evidence suggests that changes in turgor pressure are responsible for these alterations in gene expression. Expression of proU is independent of the ompR gene, known to be involved in osmoregulation of porin expression. Thus, there must be at least two distinct mechanisms by which external osmolarity can influence gene expression. We show that there are relatively few genes in the cell which are under such osmotic control. The proU gene is shown to encode a high-affinity transport system (Km = 1.3 microM) for the osmoprotectant betaine, which is accumulated to high concentrations in response to osmotic stress. Even when fully induced, this transport system is only able to function in medium of high osmolarity. Thus, betaine transport is regulated by osmotic pressure at two levels: the induction of expression and by modulation of activity of the transport proteins. We have previously shown that the proP gene encodes a lower-affinity betaine transport system (J. Cairney, I. R. Booth, and C. F. Higgins, J. Bacteriol., 164:1218-1223, 1985). In proP proU strains, no saturable betaine uptake could be detected although there was a low-level nonsaturable component at high substrate concentrations. Thus, S. typhimurium has two genetically distinct pathways for betaine uptake, a constitutive low-affinity system (proP) and an osmotically induced high-affinity system (proU).